ROOT INDUCTION IN RHODODENDRON SEMIHARDWOOD CUTTINGS TREATED WITH SOLUTION OF NAPHTHALENE ACETIC ACID - de CARVALHO, Denise Bruginski; SILVA, Lenir Maristela; ZUFFELLATO-RIBAS, Katia Christina (Scientia Agraria, 2002)
The rhododendron (Rhododendron x simsii Planch., Ericaceae) has been obtained by genetic improvement in China and it is usually propagated by cuttings. Semihardwood cuttings with approximately 10 cm of lenght were obtained from basal portion of new sprouts collected in September, 2000 from rhododendron cultivated in Setor de Ciências Biológicas of Universidade Federal do Paraná. The experiment was installed in random ized blocks with three treatments and four replications. The treatments were consisted of different NAA concentrations in watessolution (0; 2.500 and 5.000 mg.L-1) applied by imersion to the cuttings base for 15 seconds. The cuttings were kept in greenhouse under mist irrigation system in small tubes with vermiculite for 63 days. Parameters evaluated were: a) Cuttings spicuting; b) Cuttings rpcuting; c) Cuttings survival; d) Rooting pattern; e) Average length of the three longest roots. NAA application did not altered the survival percentage, sprout and rooting of rhododendron semihardwood cuttings. Beside hormonal balance, other factors are important in the root formation, because the roots of rhododendron cuttings were obtained without being treated a treatment with plant growth regulators.